Role of Calcium Therapy on Urinary Calcium/Creatinine Ratio in Healthy Pregnant Women and Pre-eclamptic Women - Moni, Sabiha Yasmin; Rashid, Mamun; Begum, Hosne Ara; Ara, Sahin; Ahmed, Nazimuddin (Bangladesh Journal of Physiology and Pharmacology, 2010)
The study has been carried out to observe the effect of calcium therapy on urinary calcium/creatinine ratio in healthy gravid women and pre-eclamptic women. Calcium/creatinine ratio has been considered for early detection of pre-eclamptic toxaemia (PET). So for the diagnosis of PET we try to investigate relation of urinary calcium, urinary creatinine, urinary calcium/creatinine ratio before and after calcium therapy. For this purpose total number of 60 healthy gravid and clinically suspected PET women of 20- 28 weeks of pregnancy having age ranged from, 17-39 years were selected. Of these 30 healthy pregnant women were taken as control group and another clinically diagnosed 30 PET women were taken as observational group. Urinary calcium/creatinine ratio was within normal range in healthy pregnant women and after calcium therapy this ratio was not significantly changed. On the other hand urinary calcium/creatinine ratio in PET women was significantly decreased and this ratio was significantly increased after calcium therapy. These observations suggest that low calcium/creatinine ratio help in early prediction of PET and calcium supplement during pregnancy may reduce the incidence of PET. DOI: 10.3329/bjpp.v25i1.5738 Bangladesh J Physiol Pharmacol 2009; 25(1&2) : 7-9